2019
DOI: 10.4274/tjod.galenos.2019.92260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reviewing childbirth scenarios on choice of delivery type: a randomized controlled trial

Abstract: Objective: The incidence of cesarean section (CS) was estimated as about 48% between 2000 and 2012 in Iran. This study was conducted to assess the effects of reviewing written childbirth scenarios on the selection of delivery method. Materials and Methods: This randomized controlled trial was conducted in Shohada Women’s Hospital in Behshahr, Mazandaran, Iran, from May to December 2015. A total of 223 women at 28 to 32 weeks of gestation were randomly allocated into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…For women in early and mid-pregnancy, 5.94% preferred CS (95% CI 5.86–5.99%; χ 2 = 194.59; df = 11 [p < 0.00001]; I 2 = 94%) [ 46 , 49 , 50 , 55 , 61 , 68 – 70 , 72 , 85 , 102 – 104 ]. Among women who were in the third trimester (late pregnancy), this proportion was 3.81% (95% CI 3.74%–3.83%; χ 2 = 549.67; df = 23[p < 0.00001]; I 2 = 96%) [ 43 , 44 , 46 , 48 , 49 , 51 , 53 – 57 , 62 , 64 , 72 , 76 , 77 , 83 , 90 , 92 , 93 , 95 , 96 , 105 ]. Preference for CS in studies that did not specify gestational age of women was 3.7% (95% CI 3.76–3.81%; χ 2 = 2865.90; df = 31 [p < 0.00001]; I 2 = 99%) [ 45 , 47 , 52 , 58 – 60 , 63 , 65 , 67 , 71 , 73 – 75 , 78 , 79 , 82 , 84 , 86 – 89 , 94 , 97 – 101 , 106 – 108 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For women in early and mid-pregnancy, 5.94% preferred CS (95% CI 5.86–5.99%; χ 2 = 194.59; df = 11 [p < 0.00001]; I 2 = 94%) [ 46 , 49 , 50 , 55 , 61 , 68 – 70 , 72 , 85 , 102 – 104 ]. Among women who were in the third trimester (late pregnancy), this proportion was 3.81% (95% CI 3.74%–3.83%; χ 2 = 549.67; df = 23[p < 0.00001]; I 2 = 96%) [ 43 , 44 , 46 , 48 , 49 , 51 , 53 – 57 , 62 , 64 , 72 , 76 , 77 , 83 , 90 , 92 , 93 , 95 , 96 , 105 ]. Preference for CS in studies that did not specify gestational age of women was 3.7% (95% CI 3.76–3.81%; χ 2 = 2865.90; df = 31 [p < 0.00001]; I 2 = 99%) [ 45 , 47 , 52 , 58 – 60 , 63 , 65 , 67 , 71 , 73 – 75 , 78 , 79 , 82 , 84 , 86 – 89 , 94 , 97 – 101 , 106 – 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for preferring CS Fourteen quantitative studies reported reasons for women’s preference for CS (Additional file 8 ) [ 49 , 56 – 58 , 60 , 72 , 81 , 82 , 85 , 87 , 95 , 97 , 99 , 107 ], which were summarized into eleven categories (Table 2 ). Across studies, the most common reasons underlying the preference for CS were pain-related fear of VB (with the proportion of women giving this reason ranging from 37.2 to 77%) [ 49 , 56 – 58 , 60 , 72 , 81 , 82 , 85 , 97 , 99 , 107 ], fear of vaginal damages (8.8 to 64.67%) [ 72 , 81 , 87 , 97 , 99 ], and the perceived risks of vaginal delivery for the baby (e.g., fear of risk for baby (6.2 to 75.33%) [ 49 , 56 , 57 , 72 , 81 , 85 , 87 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, one of the effects of training with simulated scenarios was a reduction in stress and fear of childbirth. In Rasoli et al's study to influence women's desire to choose vaginal childbirth, the use of birth scenarios in the intervention group also led to the desire of pregnant women to choose to birth their babies vaginally, influenced by reducing their fear of childbirth [ 25 ]. Interviews with 17 women who had experienced cesarean birth unearthed that one of the reasons for choosing this mode of birth was that they had previously heard stories of trauma in childbirth from relatives and friends [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is consistent with the present study. The results of several studies have shown a significant relationship between attitudes towards delivery method and level of education [6,20,26]. In the The attitude score based on the academic year (P =.001), age groups (P =.031), ethnicity (P =.001), child rank in the family (P =.042), education of the father (P =.007), the mother's education (P =.006), the mother's delivery method in other children (P =.007) and the delivery method of those around (P =.05) is significant.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery is the most important emotional event in women's life [1], and one of the most sensitive indices for the health system [2]. However for various reasons, the rate of normal vaginal delivery (NVD) has reduced [3][4][5] and the rate of cesarean section (CS) has increased over the last three decades [6]. Iran ranks first among Asian countries in terms of CS [7].…”
Section: Introductionmentioning
confidence: 99%